2010
DOI: 10.1089/ten.tea.2009.0337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Ion Concentrations on Osteogenic Differentiation and Hematopoietic Stem Cell Niche-Related Protein Expression in Osteoblasts

Abstract: Apatite biomaterials have potential not only as cell vehicles for engineering bone tissue but also as regulators of calcium (Ca) concentration in situ for controlling osteoblast functions, for example, osteogenic differentiation and fate management of hematopoietic stem cells (HSCs). To design apatite materials having optimal chemical properties for the latter purpose, more detailed investigations into what effect Ca concentrations have on osteoblast functions is crucial. In this study, osteoblasts were cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 32 publications
7
108
0
Order By: Relevance
“…Because of the importance of diffusive transport in many aspects of molecular physiology, an area currently under investigation is the design and molecular engineering of the diffusive transport properties of small molecules and ions within the hydrogel matrix as a means towards control of expressed bioactivity. Of particular importance, ion transport through hydrogels can be used within engineered scaffolds to control cell-matrix and cell-cell interactions in osteoblast cultures [11], in electro-stimulated release of bioactive compounds [12], and to maintain on-eye movement in silicone contact lenses [13]. It has been shown that diffusion in acrylate and methacrylate based hydrogels can be regulated by varying the degree of hydration [14] through the use of bi-functional monomers such as tetra(ethylene glycol) diacrylate (TEGDA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the importance of diffusive transport in many aspects of molecular physiology, an area currently under investigation is the design and molecular engineering of the diffusive transport properties of small molecules and ions within the hydrogel matrix as a means towards control of expressed bioactivity. Of particular importance, ion transport through hydrogels can be used within engineered scaffolds to control cell-matrix and cell-cell interactions in osteoblast cultures [11], in electro-stimulated release of bioactive compounds [12], and to maintain on-eye movement in silicone contact lenses [13]. It has been shown that diffusion in acrylate and methacrylate based hydrogels can be regulated by varying the degree of hydration [14] through the use of bi-functional monomers such as tetra(ethylene glycol) diacrylate (TEGDA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…[228] One of the possible causes proposed as crucial for heterotopic bone induction is the resorption/degradation with release of calcium ions having positive effect on cellular differentiation and activity. [252,[321][322][323] Consistently with literature, we observed that the ceramic inducing more bone formation (i.e. TCPS) had quicker dissolution in vitro with higher calcium ions release compared to TCPB.…”
Section: Ceramicssupporting
confidence: 89%
“…Calcium is believed to be an extra-cellular signaling molecule in bone [321][322][323] and it has been shown that ions released from calcium phosphate materials do not only enhance the bioactivity of materials [227,228,324] but also the proliferation, differentiation and mineralization of osteogenic cells. [321][322][323] We observed higher amounts of calcium ions released in vitro from 40% CaP composites compared to the others and, as shown in this study, only 40% CaP gave rise to inductive bone formation, indicating a possible role of the amount of calcium ion released in osteoinduction. The higher release of calcium ions from 40% CaP, as compared to the other three considered materials, might be due to the fact that it exposes more apatite on its surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 162 genes coding for secreted and ECM proteins were expressed by MS-5 cells cultured using condition for matrix production. These proteins are known to be involved in different HSC regulation mechanisms in the niche [61][62][63][64][65][66], explaining their ex vivo HSPC supportive behavior (Supplementary Table T3). …”
Section: Discussionmentioning
confidence: 99%